The digestion fates of lipids with different unsaturated levels in people with different age groups - Wang, Yanan; Shi, Jiachen; Xu, Yong-Jiang; Liu, Yuanfa (Elsevier BV, 2023)
The digestion behavior of lipids plays a crucial role in their nutritional bioaccessibility, which subsequently impacts human health. This study aims to investigate potential variations in lipid digestion profiles among individuals of different ages, considering the distinct physiological functions of the gastrointestinal tract in infants, aging populations, and healthy young adults. The digestion fates of high oleic peanut oil (HOPO), sunflower oil (SO), and linseed oil (LINO) were investigated using in vitro digestion models representing infants, adults, and elders. Comparatively, lipid digestion proved to be more comprehensive in adults, leading to free fatty acid (FFA) levels of 64.53%, 62.32%, and 57.90% for HOPO, SO, and LINO, respectively. Besides, infants demonstrated propensity to selectively release FFAs with shorter chain lengths and higher saturation levels during the digestion. In addition, in the gastric phase, particle sizes among the elderly were consistently larger than those observed in infants and adults, despite adults generating approximately 15% FFAs within the stomach. In summary, this study enhances our fundamental comprehension of how lipids with varying degrees of unsaturation undergo digestion in diverse age groups.